Economic and financial viability of digester use in cattle confinement for beef - Montoro, Stela B. [UNESP] (2017)
This research analyzes the economic and financial feasibility of implementing a biodigester for confinement of beef cattle on a farm located in the State of São Paulo, through the approach of discounted cash flow. The anaerobic digestion technology arouses interest, due to its advantages with the generation of electricity and the pollution reduction of water resources, soil and air, from the biogas and bio-fertilizer production, high value-added products to cattle raising. It was verified that the treatment system of cattle manure with biodigesters generate biogas and fertilizer as revenue, with free cash flows that enable a return on investment in 3.8 years and return an IRR 26.40% and an MIRR of 10.69%; all above than the minimum rate of attractiveness which confirmed the economic and financial viability of the investment.